PENGARUH PEMBELAJARAN KEWIRAUSAHAAN DAN PELATIHAN KEWIRAUSAHAAN TERHADAP MINAT BERWIRAUSAHA MAHASISWA FAKULLTAS EKONOMIKA DAN BISNIS UNIVERSITAS NEGERI SURABAYA - Syah, Wella Silvia Dian; Saino, Saino (Program Studi Pendidikan Tata Niaga Fakultas Ekonomika dan Bisnis Universitas Negeri Surabaya, 2024)
This research aims to determine the influence of entrepreneurship learning and entrepreneurship training on FEB UNESA students' interest in entrepreneurship. This research uses descriptive quantitative. The respondents in this research were 140 FEB UNESA students. The technique used is simple random sampling for sampling. Using multiple linear regression analysis to analyze data using SPSS 22.0 as a data analysis tool. From the results of data testing, it was found that: 1) entrepreneurship learning has a partial influence on the entrepreneurial interest of students at the economics and business faculty at Surabaya State University. 2) Entrepreneurship training has a partial influence on the entrepreneurial interest of students at the Faculty of Economics and Business, Surabaya State University. 3) Simultaneous entrepreneurial learning and entrepreneurship training have an influence on the entrepreneurial interest of students at the economics and business faculty of Surabaya State University.